Clarifying spiritual values among organizational development personnel - Husain, A.; Khan, A. (Academic Journals, 2010)
Values lie at the core of all human behavior. Initially, it was believed that human behavior could be best explained in terms of one's personality system, including needs, motives, beliefs, goals and attitudes. But eventually, the emphasis shifted towards values, as there are many aspects of human behavior that cannot be attributed to the former concepts, but where values play an important role. The authors believe that values make personnel life more meaningful and give them a sense of direction for organizational performance and development. In this article, the authors have discussed the sources of values, early assumptions about values, a value based approach to organizations and value assessment. Recommendations have also been offered for the human resource managers to inculcate spiritual values among personnel that may in turn be fruitful for organizational development.